2022
DOI: 10.1002/aaai.12043
|View full text |Cite|
|
Sign up to set email alerts
|

Know, Know Where, KnowWhereGraph: A densely connected, cross‐domain knowledge graph and geo‐enrichment service stack for applications in environmental intelligence

Abstract: Knowledge graphs (KGs) are a novel paradigm for the representation, retrieval, and integration of data from highly heterogeneous sources. Within just a few years, KGs and their supporting technologies have become a core component of modern search engines, intelligent personal assistants, business intelligence, and so on. Interestingly, despite large-scale data availability, they have yet to be as successful in the realm of environmental data and environmental intelligence. In this paper, we will explain why sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Specifically, we develop the EVKG based on external data sources in terms of four aspects including EV basic specifications, EV registration information, EV charging infrastructure, and electricity transmission networks. Moreover, we also link EVKG with other open-sourced KGs such as KnowWhereGraph (Janowicz et al, 2022) and GNIS-LD (Regalia et al, 2018), which are also connected with DBpedia (Auer et al, 2007), Wikidata (Vrandečić, 2012), and GeoNames (Ahlers, 2013). Three criteria are used to select EV-related data sources: (1) finer spatial resolution: EV data should be recorded in small geographic units (e.g., ZIP code level); (2) finer temporal resolution: EV data should be updated frequently (e.g., annually); and (3) reliable data resources: EV data should be collected from reliable organizations and institutions (e.g., governments and large NGOs).…”
Section: Data Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, we develop the EVKG based on external data sources in terms of four aspects including EV basic specifications, EV registration information, EV charging infrastructure, and electricity transmission networks. Moreover, we also link EVKG with other open-sourced KGs such as KnowWhereGraph (Janowicz et al, 2022) and GNIS-LD (Regalia et al, 2018), which are also connected with DBpedia (Auer et al, 2007), Wikidata (Vrandečić, 2012), and GeoNames (Ahlers, 2013). Three criteria are used to select EV-related data sources: (1) finer spatial resolution: EV data should be recorded in small geographic units (e.g., ZIP code level); (2) finer temporal resolution: EV data should be updated frequently (e.g., annually); and (3) reliable data resources: EV data should be collected from reliable organizations and institutions (e.g., governments and large NGOs).…”
Section: Data Sourcesmentioning
confidence: 99%
“…Other than these general-purpose graphs, we also have various large-scale geospatial KGs such as GeoNames (https://www.geona mes.org/; Ahlers, 2013) and KnowWhereGraph (https://knowl edgew hereg raph. org/; Janowicz, 2021;Janowicz et al, 2022) which have shown unique superiority in uplifting environmental intelligence as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One research direction in Symbolic GeoAI are Geospatial KGs (GeoKGs) (Janowicz et al, 2022;Kuhn et al, 2014). GeoKGs, as symbolic representations of geospatial knowledge, are at the core of GeoAI and facilitate many intelligent applications such as geographical question answering (Chen et al, 2013;Kuhn et al, 2021;Nyamsuren et al, 2021;Scheider et al, 2021), geospatial knowledge summarization (Yan et al, 2019), geospatial data integration (Bernard et al, 2022;Sun et al, 2021;Trisedya et al, 2019), or geographic knowledge discovery (Hu et al, 2015;Jiang et al, 2018;Li et al, 2012;Mai, Janowicz, Prasad, et al, 2020;Park & Lee, 2022).…”
Section: Symbolic Geoai: Geospatial Kgsmentioning
confidence: 99%
“…One of its aims is to develop cutting‐edge knowledge graph technologies for linking cross‐domain data for building an open knowledge network that fosters convergence research. A key research advancement in spatial sciences is the creation of KnowWhereGraph (Janowicz et al, 2022), a knowledge graph that connects environmental datasets related to natural disasters, agriculture, and soil properties to understand the environment impacts on society. Semantic enrichment services are provided to support semantic reasoning and question answering on top of its data store of over 12 billion facts (Liu, Gu, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%